The Development and Validation of Science Virtual Test to Assess 7th Grade Students' Critical Thinking on Matter and Heat Topic - Yustika Syabandari; Harry Firman; Lilit Rusyati (Universitas Pendidikan Indonesia, 2017)
An efficient way to improve the quality of education in critical thinking is developing the better tests. The test has been shifted towards the use of computer-based procedures. Lack of specific topic of critical thinking tests in science and the advanced of technology made the researcher intended to develop and validate a test to measure students’ critical thinking in the matter and heat topic based on computer for seventh grade junior high school. Generally, the process of developing and validating the test consists of 5 steps: (1) content analysis; (2) constructing multiple choice items; (3) readability test and expert validation; (4) limited tryout; and (5) larger application. Based on larger application, it is obtained the reliability value, difficulty level, discriminating power and distractor quality. The method that used in this research was descriptive. The subject was 117 students of public Junior High School in Kabupaten Bandung. The instrument validation resulted 30 items that represent 8 elements and 21 sub-elements to measure students’ critical thinking based on Inch in matter and heat topic. The instrument is further called as Science Virtual Test Matter and Heat (SVT-MH). The alpha Cronbach (α) is 0.642 which means that the instrument is sufficient to measure students’ critical thinking matter and heat topic. The result also shows the profile of students in critical thinking is 73% categorized as ‘moderate’, while students respond the positive impression towards the use of SVT-MH.KeywordsScience virtual test, critical thinking, matter and heat, readability test, validity, reliability, students’ impression